2022
DOI: 10.1007/s10971-021-05693-w
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle incorporation into flexible polyamide 12 membranes

Abstract: To meet the demands of the market and society, the development of structured polymeric materials for application in the medical field is constantly increasing. Over the last decades, metallic silver nanoparticles have been explored due to their antimicrobial action. Here, we aimed to incorporate metallic silver nanoparticles into polymeric pieces obtained by additive manufacture via a chemical route involving silver nitrate and sodium borohydride. Polyamide 12 membranes were obtained by selective laser sinteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…coli), as documented by Alnairat and co-workers . Another study also reported the incorporation of AgNPs into polyamide 12 membranes that were obtained by the selective laser sintering method that was followed by washing, pretreatment, and functionalization with alkoxides and silanes . More studies that report the use of AgNPs in polymeric membranes include the incorporation into poly(ether sulfone) membranes to develop antibacterial and antifouling ultrafiltration membranes and into polysulfone ultrafiltration membranes among others .…”
Section: Common Types Of Polymeric Nanomembranesmentioning
confidence: 81%
See 1 more Smart Citation
“…coli), as documented by Alnairat and co-workers . Another study also reported the incorporation of AgNPs into polyamide 12 membranes that were obtained by the selective laser sintering method that was followed by washing, pretreatment, and functionalization with alkoxides and silanes . More studies that report the use of AgNPs in polymeric membranes include the incorporation into poly(ether sulfone) membranes to develop antibacterial and antifouling ultrafiltration membranes and into polysulfone ultrafiltration membranes among others .…”
Section: Common Types Of Polymeric Nanomembranesmentioning
confidence: 81%
“…46 Another study also reported the incorporation of AgNPs into polyamide 12 membranes that were obtained by the selective laser sintering method that was followed by washing, pretreatment, and functionalization with alkoxides and silanes. 47 More studies that report the use of AgNPs in polymeric membranes include the incorporation into poly(ether sulfone) membranes to develop antibacterial and antifouling ultrafiltration membranes 48 and into polysulfone ultrafiltration membranes among others. 49 Zinc oxide (ZnO) nanoparticles have also been used expansively as cheap, ecological, and hydrophilic materials since they not only provide antifouling properties to the composite membranes but also provide a photocatalytic self-cleaning capability.…”
Section: Nanoparticle-based Polymericmentioning
confidence: 99%
“…Although in vitro results were the only results identified, it is worth noting that capping silver nanoparticles with poly(lactic-co-glycolic acid) and ascorbic acid can enhance their antioxidant properties and reduce their oxidant properties [131]. Furthermore, AgNPs can be incorporated into membranes, thus, practical applications are to be expected [132].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…However, AgNPs synthesized in that way have a number of drawbacks such as high cost and low stability. Typically, AgNPs are loaded onto polymers/composites in order to enhance their performance in usage [4,10,12]. Among polymers, polysaccharides have shown significant improvement in stabilization because of the hydroxy groups in the sugar molecules of the polysaccharide chain, which can form strong associations with AgNPs [13][14][15].…”
Section: Introductionmentioning
confidence: 99%